Characteristics of the immune microenvironment and their clinical significance in non-small cell lung cancer patients with ALK-rearranged mutation - Zhang, Bo; Zeng, Jingtong; Zhang, Hao; Zhu, Shuai; Wang, Hanqing; He, Jinling; Yang, Lingqi; Zhou, Ning; Zu, Lingling; Xu, Xiaohong; Song, Zuoqing; Xu, Song (Frontiers in Immunology, 2022)
Background: Although immune checkpoint inhibitors (ICIs) are one of the most important treatments for advanced-stage non-small-cell lung cancer (NSCLC), NSCLC patients with ALK-rearranged usually don’t obtain a clinical benefit. The reason may be related to the unique tumor microenvironment (TME). We evaluated the characteristics of immune biomarkers of the TME and their prognostic value in ALK-rearranged NSCLC. Methods: Tumor samples from patients with ALK-rearranged (N = 39) and EGFR- (N = 40)/KRAS- (N = 30) mutated NSCLC were collected. Immunohistochemistry (IHC) was used to assess the expression of 9 tumor immune markers as well as 6 immune markers of tumor-infiltrating cells. To research the TME of ALK-rearranged NSCLC, EGFR/KRAS-positive patients were used as controls. Furthermore, the correlation between the efficacy and prognosis of patients with advanced-stage (IIIC-IV) ALK rearrangements treated with targeted drugs was analyzed in terms of the TME. Results: The proportion of PD-L1+ tumors was lower in ALK-positive NSCLC than in KRAS-positive NSCLC. Besides, the proportion of T cells expressing TIM-3-CD8+ (15.38%), CTLA4-CD8+ (12.82%), LAG3-CD8+ (33.33%) and PD-1-CD8+ (2.56%) in ALK-positive NSCLC was lower than that in EGFR/KRAS-positive NSCLC. The expression of CD3, CD8 T cells and CD20 B cells was lower in ALK-positive NSCLC than in KRAS-positive NSCLC (p < 0.0001, < 0.005, and < 0.001, respectively). Nevertheless, the level of CD4 helper T cells was higher in ALK-positive NSCLC than in EGFR/KRAS-positive NSCLC (p < 0.0001 and p < 0.05, respectively). The repression of TIM3 was higher in ALK-positive NSCLC than in KRAS-positive NSCLC (p < 0.001). In addition, our data showed that high expression of PD-L1 (HR = 0.177, 95% CI 0.038–0.852, p = 0.027) and CTLA4 (HR = 0.196, 95% CI 0.041–0.947, p = 0.042) was related to lower OS in advanced-stage ALK- rearranged NSCLC patients treated with ALK tyrosine kinase inhibitors (TKIs). Conclusions: Immunosuppressive status was characteristic of the TME in patients with ALK-positive NSCLC compared with EGFR/KRAS-positive NSCLC. High expression of PD-L1 and CTLA4 was an adverse prognostic factor in advanced-stage ALK-rearranged NSCLC patients treated with ALK-TKIs. Immunotherapy for ALK-rearranged patients requires further exploration and validation by clinical trials.